(untitled) (World Science, 2021)
With polytrauma, more than 30% of victims are diagnosed with severe blood loss, grade III MARINO of the leading components is transfusion therapy, which aims to restore the erythron system and improve the functional state of the oxygen transport system. The addition to intensive care of substances that affect lipid peroxidation and energy status of cells can reduce the number of heterogeneous transfusions and thus reduce the number of complications in the postoperative period. Such substances may be a solution of ceruloplasmin with a leading antioxidant effect and a solution of D-fructose-1,6-diphosphate sodium salt of the hydrate with an energetic effect. Criteria for exposure to these substances should be indicators such as blood levels of hemoglobin, phosphorus, malonic dialdehyde and lactate / pyruvate ratio.